Pos Pembinaan Terpadu untuk Pemeriksaan Kesehatan Penyakit Tidak Menular pada Karyawan - Ningrum Tri Wahyuni; Sururim Maudlunah; Dwi Nur Siti Marchamah (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Non-Communicable Diseases are diseases that cannot be transmitted from person to person. Its development runs slowly over a long period, so it can cause chronic disease. Non-communicable diseases are a public health problem that causes high morbidity, disability, and mortality, and creates a burden on health financing. Therefore, it is necessary to implement prevention through comprehensive, efficient, effective, and sustainable prevention, control, and handling. The purpose of this community service is to increase employee awareness to carry out regular health checks. This community service method includes (1) Registration, (2) Interview, (3) Physical measurement, (4) Blood and psychiatric examination, (5) Identification of risk factors, counseling, and follow-up. The results of community service showed that there was high enthusiasm for non-communicable disease health examination activities for employees of the private agency located in the city of Semarang. So that it can support the program for early detection of non-communicable diseases.